(untitled) (Quinto Sol, 2021)
This article explores the process of emergence of a cultural-intellectual fraction of the elites from Córdoba, Argentina, viewed from cultural and recreational associationism. Associationism is understood as a formalized expression of the estamental sociability capable of expressing, at the same time, the tensions and transformations experienced by those elites between 1870 and 1913. We analyze two local associations, the Social Club, founded in 1871 and still existing today, and the Ateneo de Córdoba (1894-1913), showing their similarities and differences in terms of profile of the members, objectives, activities and representations linked to each association. We argue that, in addition to functioning as mechanisms for constructing social distance, such associations revealed the internal fragmentation of the elite, insofar as they contributed to delimiting a specifically cultural or intellectual fraction within the more general social elite, defined by broader socio-economic criteria. While the Club incorporated members from all fractions, the Ateneo cut down on the universe of possible members. Hence, this can illuminate neglected aspects of the diversification of the elites at the turn of the century. We worked with associative documentation such as bylaws, statutes and institutional memories, in addition to daily press and magazines.